Legal Protection for Insurance Policyholders - Khairunnisa Silalahi; Fadilla Fadwa Zailani Tumanggor; Nurcholiza Adha; Madinatul Qarima; Ahmad Zhuhri (Jurnal Sahabat ISNU SU, 2025)
To ensure certainty and security for insurance users in Indonesia, legal protection for policyholders is crucial. This study aims to determine available dispute resolution procedures, identify challenges faced, and assess legal protection measures for consumer policyholders. Using case studies and a legislative perspective, a normative legal research methodology was employed. Based on the research findings, legal protection for policyholders is regulated by the Financial Services Authority (OJK) regulations, Law Number 40 of 2014 concerning Insurance, and Law Number 8 of 1999 concerning Consumer Protection. However, customers still face several challenges in practice, including protracted and complicated dispute resolution procedures, imbalanced bargaining power, and a lack of understanding of policy terms. Court action or mediation are two options for resolving disputes. It is hoped that the presence of unambiguous legislative instruments will enable the best protection of customer rights and the development of a fair relationship between policyholders and insurance companies.